PENGARUH MANAJEMEN PEMBELAJARAN BERBASIS AI DAN PARTISIPASI BELAJAR TERHADAP KEMAMPUAN CODING SISWA MELALUI MOTIVASI BELAJAR DI SMK MUHAMMADIYAH 3 PUCANG GADING - Rulli Widiantoro; Sutama (STKIP Subang, 2026)
The advancement of Artificial Intelligence (AI) technology opens new opportunities for managing learning in vocational high schools, particularly in supporting the improvement of students' coding ability. This study aims to explore in depth the implementation of AI-based learning management, student participation, and learning motivation and their influence on students' coding ability at SMK Muhammadiyah 3 Pucang Gading. This research employed a qualitative approach with a case study design. Research subjects consisted of informatics teachers, students, and the school principal selected through purposive sampling technique. Data were collected through semi-structured in-depth interviews, participatory observation, and documentation study. Data validity was examined through source triangulation and technique triangulation. Data analysis used the interactive analysis model of Miles, Huberman, and Saldaña (2014). The results indicate that: (1) AI-based learning management at SMK Muhammadiyah 3 Pucang Gading has made a positive contribution to the development of students' coding ability through adaptive learning and automated feedback features; (2) students' active participation cognitively, emotionally, and behaviorally is the main supporting factor for successful coding learning; (3) students' learning motivation developed positively along with the implementation of AI-based learning and served as a bridge between the quality of learning management and students' coding achievement. These findings provide important implications for the development of technology-based learning policies in vocational high school settings.